2020
DOI: 10.1038/s41598-020-72355-2
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from amyloid-β exposed cell cultures induce severe dysfunction in cortical neurons

Abstract: Alzheimer’s disease (AD) is characterized by a substantial loss of neurons and synapses throughout the brain. The exact mechanism behind the neurodegeneration is still unclear, but recent data suggests that spreading of amyloid-β (Aβ) pathology via extracellular vesicles (EVs) may contribute to disease progression. We have previously shown that an incomplete degradation of Aβ42 protofibrils by astrocytes results in the release of EVs containing neurotoxic Aβ. Here, we describe the cellular mechanisms behind EV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
2
38
0
Order By: Relevance
“…Additionally, in both homeostatis as well as disease state astrocyte derived EVs (ADEVs) have been shown to play critical roles in modulating cellular functions in the CNS [43,44]. In AD, EVs carrying amyloid cargoes have been postulated to serve as biomarkers of disease pathogenesis [45] while also playing a role in seeding of amyloids, thus disseminating the disease [46], leading to disease progression and severity [47][48][49].…”
mentioning
confidence: 99%
“…Additionally, in both homeostatis as well as disease state astrocyte derived EVs (ADEVs) have been shown to play critical roles in modulating cellular functions in the CNS [43,44]. In AD, EVs carrying amyloid cargoes have been postulated to serve as biomarkers of disease pathogenesis [45] while also playing a role in seeding of amyloids, thus disseminating the disease [46], leading to disease progression and severity [47][48][49].…”
mentioning
confidence: 99%
“…Astrocytes, microglia, and co-cultures were exposed to 0.5 μM αSYN-F or 0.2 μM Aβ-F for 24h, 4d, or 7d. The concentrations were selected based on our previous studies [ 11 , 12 , 23 , 28 , 29 ]. The lower concentration of Aβ was used since aggregated Aβ is more toxic to astrocytes than aggregated αSYN.…”
Section: Methodsmentioning
confidence: 99%
“…In sum, these studies confirmed the transport of Aβo, APP, and its cleaved products in exosomes and their further uptake and internalization by neuronal cells. Moreover, the neurotoxic effects of adding exosomes derived from AD human plasma, cell, and animal models or previously exposed to toxicity-inducing Aβ-protofibrils has also been described ( Eitan et al, 2016 ; Beretta et al, 2020 ).…”
Section: Critical Roles Of Exosomes In Neurological Disordersmentioning
confidence: 99%